A Case Report of A Life-Threatening Condition: Complete Heart Block Induced By Systemic Lupus Erythematosus - Puji Rachmawan, Yogi; Pramudya, Arsha; Pratiwi, Witri; Irnizarifka, Irnizarifka; Imani, Fawzia Haznah Nurul (Syntax Corporation Indonesia, 2026)
Systemic lupus erythematous is often accompanied by complications in the cardiovascular system such as pericarditis, valvular disease, coronary artery disease, but complications in the conduction pathway are rare condition. Conduction system disorders such as complete heart block can cause life-threatening conditions and require immediate treatment. This case report describes a 43-year-old woman who presented with syncope and complete heart block. The patient received high-dose corticosteroid therapy but the complete heart block did not improve so a permanent pacemaker was implanted. This case showed that SLE complications in the cardiovascular system including the cardiac conduction system must be watched out for because it is a life-threatening condition.